Innovative Trigonometry Learning: The Role of Liveworksheets-assisted Interactive Worksheets in Improving Numerical Literacy - Basir, Mochamad Abdul; Agustyani, Mayana; Maharani, Hevy Risqi (Department of Mathematics Education Program IPI Garut, 2024)
Penelitian pengembangan lembar kerja interaktif berbasis teknologi masih sangat terbatas. Penelitian bertujuan mengembangkan lembar kerja interaktif berbantuan Liveworksheets sebagai upaya meningkatkan literasi numerasi siswa yang memenuhi kriteria valid, praktis, dan efektif. Kevalidan lembar kerja interaktif dinilai oleh ahli media dan ahli materi. Kepraktisan penggunaan lembar kerja interaktif berdasarkan respon guru dan siswa. Keefektifan implementasi pembelajaran trigonometri menggunakan lembar kerja interaktif ditinjau dari hasil peningkatan pretest dan postest kemampuan literasi numerasi siswa. Penelitian pengembangan menggunakan model ADDIE, meliputi Analyze, Design, Development, Implementation, dan Evaluation. Hasil penelitian menunjukkan Lembar kerja Interaktif berbantuan Liveworksheets valid dengan skor 86% ​​dari ahli media dan 80% dari ahli materi. Penggunaan lembar kerja interaktif berkategori sangat praktis dengan skor 94,80% dari angket respon guru dan 84,60% dari angket respon siswa. Pembelajaran menggunakan lembar kerja interaktif berbantuan Liveworksheets efektif meningkatkan literasi numerasi siswa. Bantuan scaffolding berbasis teknologi yang diterapkan pada pembelajaran menggunakan liveworksheet menjadi lebih menarik dan memotivasi siswa untuk berpikir literasi numerasi.Research on the development of technology-based interactive worksheets is still minimal. The study aims to develop interactive worksheets assisted by Liveworksheets to improve students' numeracy literacy that meets the criteria of valid, practical, and effective. Media experts and material experts assess the validity of interactive worksheets. The practicality of using interactive worksheets is based on teacher and student responses. The effectiveness of implementing trigonometry learning using interactive worksheets is reviewed from the results of the pretest and posttest increase in students' numeracy literacy skills. The development research uses the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The study results showed that the Interactive Worksheet assisted by Liveworksheets was valid, with 86% validity from media experts and 80% from material experts. Interactive worksheets are categorized as very practical, with a score of 94.80% from the teacher response questionnaire and 84.60% from the student response questionnaire. Learning using interactive worksheets assisted by Liveworksheets effectively improves students' numeracy literacy. Technology-based scaffolding assistance applied to learning using liveworksheets makes it more interesting and motivates students to think about numeracy literacy.